2020
DOI: 10.1186/s40168-020-00847-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria pathogens drive host colonic epithelial cell promoter hypermethylation of tumor suppressor genes in colorectal cancer

Abstract: Background Altered microbiome composition and aberrant promoter hypermethylation of tumor suppressor genes (TSGs) are two important hallmarks of colorectal cancer (CRC). Here we performed concurrent 16S rRNA gene sequencing and methyl-CpG binding domain-based capture sequencing in 33 tissue biopsies (5 normal colonic mucosa tissues, 4 pairs of adenoma and adenoma-adjacent tissues, and 10 pairs of CRC and CRC-adjacent tissues) to identify significant associations between TSG promoter hypermethylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 56 publications
4
79
0
Order By: Relevance
“…This is in accordance with Jørgensen et al (45), who observed the enrichment of genus Hungatella in 16S rRNA microbiome of CVID patients. H. hathewayi is a part of the normal human intestinal microflora (44,46,47), but it is also involved in various human infections (48)(49)(50), and its abundance was increased among patients suffering from cystic fibrosis (51), primary IgA nephropathy (52), chronic kidney disease (53), and colon cancer (54)(55)(56).…”
Section: Cvid Microbiota Shows Subtle Differences On a Species Levelmentioning
confidence: 99%
“…This is in accordance with Jørgensen et al (45), who observed the enrichment of genus Hungatella in 16S rRNA microbiome of CVID patients. H. hathewayi is a part of the normal human intestinal microflora (44,46,47), but it is also involved in various human infections (48)(49)(50), and its abundance was increased among patients suffering from cystic fibrosis (51), primary IgA nephropathy (52), chronic kidney disease (53), and colon cancer (54)(55)(56).…”
Section: Cvid Microbiota Shows Subtle Differences On a Species Levelmentioning
confidence: 99%
“…Recently, several independent studies have showed the important role of gut microbiota in influencing immunotherapy response in patients with melanoma, non-small cell lung cancer, and renal cell carcinoma 7 - 11 , which provides us a new target to influence the anti-PD-1 mAb outcomes. Meanwhile, studies have suggested that altered gut microbiota are closely associated with occurrence and development of CRC 12 - 14 and CRC patients are characterized by decreased richness and diversity, and significantly disturbed gut microbiota 15 . However, it remains uncertain how to modulate these gut microbiota dysbiosis to improve the anti-PD-1 mAb efficacy in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed we could be seeing these effects upon looking at the microbes correlating with significantly abundant host genes in CRC samples from PRJNA413956. While C. lusitaniae is an opportunistic pathogen causing candidemia (Desnos-Ollivier et al, 2011;Krcmery et al, 1999) possibly exploiting the lowered immune responses in cancer patients (Aslani et al, 2018), and some Streptococcus species have previously been implicated in CRC (Kumar et al, 2017;Xia et al, 2020) with S. pyogenes having been known to cause invasive infections in humans (Parks et al, 2015), Cupriavidus necator (formerly known as Ralstonia eutropha (Reinecke and Steinbüchel, 2009)) is a soil bacterium that may be a sequencing contaminant in this dataset. Cupriavidus and Ralstonia species have been previously identified as common contaminants in metaomics studies (Guo et al, 2019;Salter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%